2018
DOI: 10.1002/bit.26527
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the sodium‐potassium ratio as a lever for controlling cell growth and improving cell specific productivity in perfusion CHO cell cultures

Abstract: Perfusion processes typically require removal of a continuous or semi-continuous volume of cell culture in order to maintain a desired target cell density. For fast growing cell lines, the product loss from this stream can be upwards of 35%, significantly reducing the overall process yield. As volume removed is directly proportional to cell growth, the ability to modulate growth during perfusion cell culture production thus becomes crucial. Leveraging existing media components to achieve such control without i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Suppression of cell growth at high viabilities and productivities is especially important when bleed rates in steady‐state perfusion need to be minimized in order to prevent product loss. Such attempts to decouple productivity from growth were already proven by media additives such as small molecule cell growth inhibitors, or altered sodium–potassium levels to arrest cells in the G0/G1 phase . Alternatively, process control strategies were used to keep cells in a physiological state using lactate consumption and the resulting rise in culture pH to regulate perfusion media addition or minimizing growth and maximize productivity by reduced culture temperatures or limiting CSPR .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of cell growth at high viabilities and productivities is especially important when bleed rates in steady‐state perfusion need to be minimized in order to prevent product loss. Such attempts to decouple productivity from growth were already proven by media additives such as small molecule cell growth inhibitors, or altered sodium–potassium levels to arrest cells in the G0/G1 phase . Alternatively, process control strategies were used to keep cells in a physiological state using lactate consumption and the resulting rise in culture pH to regulate perfusion media addition or minimizing growth and maximize productivity by reduced culture temperatures or limiting CSPR .…”
Section: Resultsmentioning
confidence: 99%
“…Such attempts to decouple productivity from growth were already proven by media additives such as small molecule cell growth inhibitors, or altered sodium-potassium levels to arrest cells in the G0/G1 phase. 17 Alternatively, process control strategies were used to keep cells in a physiological state using lactate consumption and the resulting rise in culture pH to regulate perfusion media addition 18 or minimizing growth and maximize productivity by reduced culture temperatures 19,20 or limiting CSPR. 21 Culture pH, pCO 2 levels, and osmolality were also shown to profoundly impact cell growth and productivity 22,23 and may be used for future perfusion control strategies.…”
Section: Suppression Of Cell Growth At High Viabilities and Productivmentioning
confidence: 99%
“…There exist more than 100 types of preservation solutions in the field of organ transplantation , and we included only Euro‐Collins solution in this study and did not compare other widely used preservation solutions such as University of Wisconsin, histidine‐tryptophan‐ketoglutarate, Celsior or Perfadex . These preservation solutions, which have demonstrated the ability to facilitate the organ viability and function during refrigerated storage, also can be beneficial during tissue transport for the isolation and culture of adult cells; however, considering the potential impairment of cell proliferation in high extracellular potassium concentration conditions substantiated by our results and previous investigations , care should be taken when using ICF‐type solution for tissue preservation. Another limitation is that the tissue stem cell function after preservation was examined only by comparing the colony formation ability of lung mesenchymal stem cells whose origin and function are still controversial .…”
Section: Discussionmentioning
confidence: 74%
“…The time‐course potassium concentration was also observed to be lower than historical process experience and further review of the formulation changes showed an adjustment in the potassium phosphate concentration as well. It was hypothesized that the change in the ratio of sodium and potassium may have resulted in a change in the function of the Na + ‐K + ‐ATPase, which modulates a variety of cellular functions from growth to nutrient uptake such as glutamate and aspartate . As a confirmation, potassium phosphate and sodium (as sodium chloride) were restored to the same molar ratio as in version 1 of the powder which resulted in a complete restoration of the biocapacitance profile driving historically comparable feed totals, titer, and osmolality (Figure ).…”
Section: Resultsmentioning
confidence: 99%